Mitochondrial function in rat cerebral cortex and hippocampus after short- and long-term hypobaric hypoxia - Czerniczyniec, Analia (2015)
Taking into account the importance of aerobic metabolism in brain, the aim of the present work was to evaluate mitochondrial function in cerebral cortex and hippocampus in a model of sustained hypobaric hypoxia (5000 m simulated altitude) during a short (1 mo) and a long (7 mo) term period, in order to precise the mechanisms involved in hypoxia acclimatization. Hippocampal mitochondria from rats exposed to short-term hypobaric hypoxia showed lower respiratory rates than controls in both states 4 (45%) and 3 (41%), and increased NO production (1.3 fold) as well as eNOS and nNOS expression associated to mitochondrial membranes, whereas mitochondrial membrane potential decreased (7%). No significant changes were observed in cortical mitochondria after 1 mo hypobaric hypoxia in any of the mitochondrial functionality parameters evaluated. After 7 mo hypobaric hypoxia, oxygen consumption was unchanged as compared with control animals both in hippocampal and cortical mitochondria, but mitochondrial membrane potential decreased by 16% and 8% in hippocampus and cortex respectively. Also, long-term hypobaric hypoxia induced an increase in hippocampal NO production (0.7 fold) and in eNOS expression. A clear tendency to decrease in H2O2 production was observed in both tissues. Results suggest that after exposure to hypobaric hypoxia, hippocampal mitochondria display different responses than cortical mitochondria. Also, the mechanisms responsible for acclimatization to hypoxia would be time-dependent, according to the physiological functions of the brain studied areas. Nitric oxide metabolism and membrane potential changes would be involved as self-protective mechanisms in high altitude environment.